2008
DOI: 10.1162/jocn.2009.21047
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral White Matter Integrity Mediates Adult Age Differences in Cognitive Performance

Abstract: Previous research has established that age-related decline occurs in measures of cerebral white matter integrity, but the role of this decline in age-related cognitive changes is not clear. To conclude that white matter integrity has a mediating (causal) contribution, it is necessary to demonstrate that statistical control of the white matter-cognition relation reduces the magnitude of age-cognition relation. In this research, we tested the mediating role of white matter integrity, in the context of a task swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
254
4
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(291 citation statements)
references
References 66 publications
31
254
4
2
Order By: Relevance
“…The present results confirm a relationship between mRT from the congruent condition and DTI parameters, in that significant effects were seen for AD and MD in the genu and middle sections (body) of the corpus callosum, and in the left anterior thalamic radiation and forceps minor for AD. Several studies report that various measures of information processing speed are related to microstructural characteristics of WM in the genu of corpus callosum (Bucur et al, 2008;Madden et al, 2009), in agreement with the present results from the congruent condition. However, the anatomical locations and which DTI parameter shows the strongest effects vary between studies, likely partly due to different cognitive tasks.…”
Section: Wm Characteristics and Information Processing Speedsupporting
confidence: 92%
See 2 more Smart Citations
“…The present results confirm a relationship between mRT from the congruent condition and DTI parameters, in that significant effects were seen for AD and MD in the genu and middle sections (body) of the corpus callosum, and in the left anterior thalamic radiation and forceps minor for AD. Several studies report that various measures of information processing speed are related to microstructural characteristics of WM in the genu of corpus callosum (Bucur et al, 2008;Madden et al, 2009), in agreement with the present results from the congruent condition. However, the anatomical locations and which DTI parameter shows the strongest effects vary between studies, likely partly due to different cognitive tasks.…”
Section: Wm Characteristics and Information Processing Speedsupporting
confidence: 92%
“…Due to the spatial distribution of highly specialized brain areas (Gläscher et al, 2010) and that the main function of the myelin sheet is to isolate the axons, thereby facilitating conduction of action potentials over long distances, individual differences in WM structure are expected to affect cognitive performance, e.g., processing speed (O'Sullivan et al, 2001;Madden et al, 2004Madden et al, , 2009Schulte et al, 2005;Deary et al, 2006;Grieve et al, 2007;Bucur et al, 2008;Correia et al, 2008;Turken et al, 2008;Kennedy and Raz, 2009;Vernooij et al, 2009). The present results confirm a relationship between mRT from the congruent condition and DTI parameters, in that significant effects were seen for AD and MD in the genu and middle sections (body) of the corpus callosum, and in the left anterior thalamic radiation and forceps minor for AD.…”
Section: Wm Characteristics and Information Processing Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, forceps major is not assumed to be especially important for cognitive control. This assumption does not exclude the possibility that maturation of specific WM tracts can be related to more specific cognitive functions (57)(58)(59)(60), but it will likely also have general beneficial effects on major cognitive functions through facilitation of processing speed (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
“…35 and 36) and it has been proposed that age-associated declines in WM and long-term memory are a result of reorganization in the functional integration of brain regions, in addition to general dysfunction of specific regions and white matter connections (37)(38)(39). For example, Grady et al (40) showed that functional connectivity between the hippocampus and prefrontal cortex differs between younger and older adults, such that older adults exhibit connectivity to more dorsolateral areas (rather than ventral areas) in the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%